Bioindicadores fitoplanctônicos da qualidade da água no Estuário do Rio Catu, Aquiraz, Ceará - Pereira, Antônio Cícero de Andrade (2007)
The estuaries are semi closed coastal ecosystems, which reflect a great variation of the physical-chemical parameters influenced by the tides and, consequently, reflecting on the distribution and flotation of the abundance of the aquatic communities. Since they are subjected to excessive nutrition, which generally comes from wastewater, they are able to start an eutrophication process which can be beneficial or they can turn into an inappropriate body of water for any human activity. This paper objected to analyze the seasonal occurrence of phytoplankton bioindicators of the water quality in the estuary of the Catu River, Aquiraz, Ceará, verifying the variations of the primary productivity and the physical-chemical parameters to which this occurrence is generally associated to. Monthly collections were held from January until December 2005, in the region of Catu´s River mouth in order to obtain the data referring to the water and air temperature, transparency, depth, salinity, pH, ammonia, nitrite, oxygen and dissolved CO2, phosphate and silicate, as well as, data from the biological material. The results showed that, with the exception of the ammonia values, nitrite, phosphate and silicate, the other environmental parameters were found under the recommended patterns. The primary productivity was considered to be very low. 19 families and 32 genera were identified, making the identification of 12 species possible up to the taxon species. These phytoplankton representatives are inserted in the Cyanophyceae, Chlorophyceae, Baccillariophyceae, Dinophyceae, Zygnemaphyceae, Chlamydophyceae classes, in which the Cyanophyceae were the most abundant in the rainy season and the Baccillariophyceae were more abundant in the dry seasons. The Anabaena cylindrica was dominant in the rainy season and all the other species were rare. In the dry season Navicula sp. was classified as abundant and Nitzschia sp. and Anabaena cylindrica were not so abundant. The physical-chemical conditions, the presence of biological indicators of the phytoplankton, besides the registered blooms of Anabaena cylindrica, showed that the estuarine waters presented an advanced state of artificial eutrophication